The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0104-42302008000600017
|View full text |Cite
|
Sign up to set email alerts
|

Hospital: valores éticos que expressam sua missão

Abstract: elma@usp.br RESUMO INTRODUÇÃO. O hospital é uma organização com responsabilidades éticas especiais que não podem ser comprometidas quando da incorporação de traços empresariais em sua estruturação. Este artigo traz resultados de pesquisa documental, qualitativa, exploratória, descritiva que teve como objeto valores institucionais dos hospitais. OBJETIVOS. Identificar, na literatura, valores esperados para hospitais; identificar valores declarados pelos hospitais em suas páginas na internet e compará-los com a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 4 publications
1
3
0
3
Order By: Relevance
“…Thus, from their values some hospitals deduce the principles, which operationalize in rules governing the action. However, because of the difficulty in establishing watertight compartments between values and principles, we agree with Anunciação and Zoboli [9] who, in their research, used principles and values as synonyms. We have therefore almost homogeneous contents and sometimes even overlapping, between the mission, values and vision directed to the quality of health care, clinical area and the technical and organizational management, valuing the person in its dignity, with a strong focus on the ethical paradigm of personalism, responsibility and care.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Thus, from their values some hospitals deduce the principles, which operationalize in rules governing the action. However, because of the difficulty in establishing watertight compartments between values and principles, we agree with Anunciação and Zoboli [9] who, in their research, used principles and values as synonyms. We have therefore almost homogeneous contents and sometimes even overlapping, between the mission, values and vision directed to the quality of health care, clinical area and the technical and organizational management, valuing the person in its dignity, with a strong focus on the ethical paradigm of personalism, responsibility and care.…”
Section: Discussionsupporting
confidence: 84%
“…In the research of Anunciação and Zoboli [9] the values found in literature and on the web sites of 30 hospitals in Brazil have been grouped in the following categories: assistance, administration and social commitment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assim, torna-se imprescindível que o hospital seja regido por princípios éticos (Anunciação, Zoboli, 2008 (Bandeira, Marques, Veiga, 2000). A forma como o empregado se comporta e se envolve estabelecendo um vínculo psicológico com a organização e se identificando com a cultura, valores e políticas internas, compreende o seu comprometimento organizacional (Meyer, Allen, Smith,1993).…”
Section: Identificação Dos Conflitos éTicos Gerenciais Dos Enfermeirosunclassified